Design and Implementation of Home Security Using Telegram Botfather - Asef Duwi Kurniawan (Universitas Nusa Putra, 2020)
Security is a condition where humans or objects feel protected from the danger that threatens or disturbs them, which will then cause a feeling of calm and comfort. Security can be obtained in several ways, one of which is by using and implementing technology. Today's application of security technology has developed very rapidly, ranging from conventional methods to high-tech. Therefore the author tries to design a home security system based on a microcontroller which is expected to be helpful, especially for people who often travel out of the house. One of the contributions made is to design and manufacture a home security device using the BOTFather telegram. This home security system uses internet technology to control devices remotely. Nodemcu esp8266, PIR sensor as a sensor used to detect infrared rays from an object, PIR sensor is passive, meaning that this sensor does not emit infrared light but only receives infrared radiation from outside. 4 channel relay is a switch that is entirely operated with electricity and is an electromechanical (electromechanical) component consisting of 2 parts, namely electromagnet (coil) and mechanical (separate lift contact switch/switch) which is used to turn on and off lights, and other devices. Arduino software is used to program Nodemcu Esp8266. PIR sensors, Lamp Relays and TELEGRAM are used as tools to send commands to devices in real-time